UPAYA REBOISASI POHON MAHONI DI DESA GARUNGGANG KECAMATAN KUALA KABUPATEN LANGKAT - Sinarsi Sinarsi; Frida Liharris Saragih; Sondang Purba (Community : Jurnal Pengabdian Pada Masyarakat, 2022)
Floods and landslides often occur in Garunggang Village, Kuala District, Langkat Regency, North Sumatra. Flood is an event where land that is usually dry (not swampy area) becomes inundated by water, this is caused by high rainfall and the topographical conditions of the area in the form of low to sunken land. To prevent floods and landslides, mahogany trees were planted in the watershed of Garunggang village, Kuala sub-district, Langkat district. This activity was opened by the presenter, after that singing the Indonesia Raya anthem, welcoming remarks, signing the cooperation and continued with tree planting and group photos. Efforts to plant mahogany trees in the watershed of Garunggang village, Kuala District, Langkat Regency. This activity was welcomed by the community in an effort to reforest the planting of mahogany trees in the watershed of Garunggang village, Kuala District, Langkat Regency. So it can be concluded that this activity has a good impact and influence on people's knowledge in preserving the natural environment in the Upstream Wampu watershed area, Garunggang Village. Let's take care of our environment together, hopefully in the future, this activity can be more useful for the surroundings.